Spectrophotometric simultaneous analytical method validation to determine isoniazid and pyridoxine in pure and 3D printed tablet forms - Sudarman, Nur Suhaila; Haris @ Harith, Muhammad Salahuddin (IIUM Press, 2023)
Introduction: Isoniazid (INH) is the anti-tuberculosis drugs being used to counter tuberculosis since 1952. Patients on INH should be given daily prophylactic pyridoxine (PYR) with 10-50 mg/day to prevent the development of isoniazid-induced neuropathy. Within the framework of this research, the UV-Vis spectrophotometer is used to quantify simultaneously the drug content of INH and PYR. Methods: The standard curve for both INH and PYR were plotted using the concentration of 5 μg/ml, 10 μg/ml, 15 μg/ml, 20 μg/ml, 25 μg/ml, and 30 μg/ml and tablets were analysed using simultaneous equation method. The proposed method was validated by analytical method validation for the linearity, specificity, accuracy, intermediate precision, limit of detection (LOD), and limit of quantification (LOQ). Results: A regression equation of INH standard and sample were found to be y = 0.0279x + 0.0637 and y = 0.0280x + 0.0522 obtained from the calibration curve and linear with correlation coefficient (R2) values of 0.9950 and 0.9964, respectively. A regression equation of PYR standard and sample were y= 0.0267x + 0.0723 and y = 0.0259x + 0.0806 and to be linear with R2 values of 0.9981 and 0.9962, respectively. The result of accuracy obeyed the accepted criteria of percentage recovery in % to 102%. The method exhibited intermediate precision as demonstrated by relative standard deviation <2%. The LOD and LOQ of INH were 0.166 μg/ml and 0.5018 μg/ml while the LOD and LOQ of PYR were 0.122 μg/mL and 0.371 μg/mL, respectively in the pure form. In tablet dosage form, the LOD and LOQ of INH were 0.071μg/ml and 0.215 μg/m while LOD and LOQ of PYR give the result 0.124 μg/ml and 0.375 μg/ml, respectively. Conclusion: This spectrophotometric simultaneous analytical method validation for INH and PYR was successfully conducted with the notion to spearhead the development of INH and PYR in a single dosage form to improve compliance among tuberculosis patients.